The Effect of Setting-Culture Interaction on the Vocational Education of American Indians - Jim C. Fortune; Stephanie Blecarczyk (Journal of Research in Rural Education, 1983)
The theme of the paper addresses the interaction of cultural beliefs, community needs and setting characteristics on the design and evaluation of vocational projects. The paper utilizes, as a case study completed by the authors, one of several evaluations of vocational projects on or near Indian reservations. Definite influences were found in these evaluations, and the effects of these influences suggest a new perspective in project design and evaluation. Implications for nature of goals, expectations of success, choice of evaluation criteria, and interpretation of evaluation results are discussed.